Eksternalitas Pertambangan Emas Rakyat di Kabupaten Buru Maluku - Una Selvi Tuaputy; Eka Intan Kumala Putri; Zuzy Anna (Departemen Ekonomi Sumberdaya dan Lingkungan, Fakultas Ekonomi dan Manajemen, Institut Pertanian Bogor, 2014)
Gold mining carried out in the Buru Regency, “Gunung Botak”, has been held since 2012. The mining regulations are governed by local governments. The aims of this research were: 1) to identify and estimate the cost of gold mining transactions, 2) to identify and estimate WTP WTP transaction costs and improve the quality of the environment, and 3) to know the public perception about the existence of the mine. 4) to identify the value of externalities of gold mining activities.of illegal gold mining activities The methods analysis used was statistical analysis approach, the analysis of changes in the analysis of willingness to pay (WTP) with CVM models, multiple regression analysis of linear logistic and multiple regression analysis. The results of this study were: 1) The entry fee to the mining was set by the local government in Kayeli plains known by the King (the head of Kayeli village). The entry fee for the male miners was Rp.750.000/ person per-three months, whereas it was Rp.500.000/ person per three months for women miners. 2) The desire to pay for the improvement of environmental quality was RP.430.000/ person/ month. 3) The public perception of the existence of gold mining was that 20 respondents chose the mining to close and 24 respondents chose the mining to open, 4) the value of exstenalities taken from gold mining activities was IDR.131.803.251.922.